Seed and seedling variation amongst provenances in Faidherbia albida - Ibrahim, A; Fagg, C; Harris, S (1997)
Seed and seedling morphology of Faidherbia albida was investigated in conjunction with isozyme analysis. Seeds from 19 seed lots representing central, western and southern parts of the distribution range were studied. The results are in accordance with the earlier discovery of two distinguishable ecogeographical races. The isozyme locus Sod-2 shows two different phenotypic patterns over the geographical range of the species. One phenotypic pattern was confined to the central arid western parts of the distribution range (the Sahelian range) and the other to the southern part of the range, although the two patterns were found to overlap in north-eastern Ethiopia. A similar bimodal pattern of variation was also shown in the seed and seedling morphology; one phenotype appears to be endemic to the southern part of the distribution range, whilst the other appears to be endemic to the Sahelian range. Clines of some morphological traits investigated were also evident in the riparian habitat of the central distribution range (the Nile (N)). Based on the results, recommendations pertaining to the utilisation of the species gene resources and stand establishment were inferred.